2019
DOI: 10.29252/nfsr.6.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic and Hypolipidemic Effects of Myrtus communis, Trachyspermum copticum and Ferula gummosa Essential Oils on Streptozotocin Induced Diabetic Rats

Abstract: Background and Objectives: Diabetes is one of the major health challenges in world. Herbal medicines are widely used for the treatment of diabetes. The current study assessed the effects of oral administration of essential oils from Myrtus communis, Trachyspermum copticum and Ferula gummosa on blood glucose and lipid profiles in streptozotocininduced diabetic rats and inhibitory effects of these oils on α-glucosidase activity in vitro. Materials and Methods: Forty-eight male Wistar rats were divided into six g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…M. communis leaf aqueous extract was investigated for antidiabetic and antioxidant effects in diabetic rats induced with streptozotocin (STZ) and normal rats. MC leaf aqueous extract given at 150, 300, and 600 mg/kg significantly reduced ALT, AST, ALP in serum blood glucose and MDA levels, in STZ-induced diabetic rats when compared to controls groups ( P <0.05) (Karimlar et al 2019 ).…”
Section: Antidiabetic Effectmentioning
confidence: 96%
“…M. communis leaf aqueous extract was investigated for antidiabetic and antioxidant effects in diabetic rats induced with streptozotocin (STZ) and normal rats. MC leaf aqueous extract given at 150, 300, and 600 mg/kg significantly reduced ALT, AST, ALP in serum blood glucose and MDA levels, in STZ-induced diabetic rats when compared to controls groups ( P <0.05) (Karimlar et al 2019 ).…”
Section: Antidiabetic Effectmentioning
confidence: 96%
“…The model-fitting results showed that BEO-loaded zein nano-fibers could be a delivery vehicle for diabetes control. Karimlar et al,(2019) exposed the hypoglycemic and hypolipidemic effects of three medicinal plants' essential oils including F. gummosa on streptozotocin-induced diabetic rats. For the experimental setup the streptozotocin-induced (45 mg/kg doses, intraperitoneally) male wistar rats were used and treated with the essential oil (200 mg/kg/day).…”
Section: Hypoglycemic and Hypolipidemic Effectmentioning
confidence: 99%